Let’s Address Hatred by Identifying Its Various Aspects and Appreciating the Usefulness of Different Tools and Interventions Aimed at Tackling Its Numerous Forms and Manifestations: A Systematic Review - Salman Shafiq (BJPsych Open)
Aims: Hatred can manifest in several ways. This article aims to explore what information can be obtained from the medical literature to address a variety of manifestations and expressions of hatred.